The Influence of Transformational Leadership on Employee Performance at The Kutambaru District Office - Anta Tarigan, Edy; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of transformational leadership on employee performance at the Kutambaru District Office. This research was carried out at the Kutambaru District Office. The type of research is associative quantitative. The sample in this study was 15 employees with ASN and honorary status at the Kutambaru District Office. The sampling technique in this study used the entire population of 15 people. The research results show that Transformational Leadership has a significant influence on employee performance as shown by the T-Statistic value of 4.104 > 1.753 and the P Value of 0.001 < 0.05. This shows that improvements in Transformational Leadership can improve employee performance at the Kutambaru District Office.